Conception of strategic cooperation between universities and community elderly service centers - Wu Jing (SHS Web of Conferences, 2022)
At present, about 90% of the elderly in the country choose to live at home. For various reasons, many elderly people feel lonely, even with children around. Using the methods of questionnaire survey and indepth interviews, this paper visited the elderly service centers in 15 communities in Wuhan, and conducted a questionnaire survey on 412 elderly people over 60 years old. The results showed that 54% of the elderly often go to community elderly service centers to participate in activities, but 30% of the elderly never go; the elderly who go to the community have the highest satisfaction with community entertainment activities such as mahjong room and square dance, 50%are satisfied; elderly people with higher education level are less likely to participate in community activities; the elderly generally lack spiritual comfort; 37% of them want to use their expertise to contribute to the community but do not know how to start. To this end, this paper proposes to take advantage of Wuhan’s 83 colleges and universities to seek strategic cooperation between universities and neighboring communities, so that relatively young healthy elderly people aged 60-75 can have lifelong learning opportunities and continue their spiritual growth. At the same time, it promotes the effective combination of theoretical knowledge and social practice of teachers and students in universities. This move will enhance the social participation and well-being of the elderly and promote the construction of an elderlyfriendly society.